2019
DOI: 10.1152/ajpcell.00125.2019
|View full text |Cite
|
Sign up to set email alerts
|

Orexins alleviate motor deficits via increasing firing activity of pallidal neurons in a mouse model of Parkinson’s disease

Abstract: Orexin is a peptide neurotransmitter released in the globus pallidus. Morphological evidence reveals that both orexin 1 receptor (OX1R) and orexin 2 receptor (OX2R) exist in the globus pallidus. Here we showed that bilateral microinjection of both orexin-A and orexin-B into the globus pallidus alleviated motor deficits in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced parkinsonian mice. Further in vivo extracellular single-unit recording revealed that the basal spontaneous firing rate of the globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…There was no specific time point given in this study as to when orexin neuron loss was measured as the protocol timeframe varied (Fifel et al., 2014). In an MPTP PD model in mice, no orexin loss was also found when compared to controls; however, there was no timeline as to when orexin neurons loss was measured (Wang et al., 2019). From 6‐OHDA studies, it appears that orexin neuron loss occurs at later stages (after 40–60 days); therefore, the MPTP animal models may need to be repeated with longer timeframes.…”
Section: Orexin In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no specific time point given in this study as to when orexin neuron loss was measured as the protocol timeframe varied (Fifel et al., 2014). In an MPTP PD model in mice, no orexin loss was also found when compared to controls; however, there was no timeline as to when orexin neurons loss was measured (Wang et al., 2019). From 6‐OHDA studies, it appears that orexin neuron loss occurs at later stages (after 40–60 days); therefore, the MPTP animal models may need to be repeated with longer timeframes.…”
Section: Orexin In Pdmentioning
confidence: 99%
“…In a recent study on MPTP‐induced mice, the mice exhibited motor deficits and the intracerebroventricular (ICV) administration of orexin B increased general spontaneous activity and alleviated motor coordination deficits (Bian et al., 2021). Another study on MPTP PD‐induced mice found that motor deficits were reversed and pallidal neuron (which are involved in regulating proprioceptive and conscious movement) spontaneous firing rates were increased with the injection of orexin A and orexin B into the globus pallidus (Wang et al., 2019). Consistently, in MPTP PD‐induced mice, the administration of orexin A reversed motor deficits shown by significantly reducing the t‐turn time (time to turn downward from the top of the pole) in the pole test and significantly increasing the total distance traveled in the open field test (Liu et al., 2018).…”
Section: Orexin In Pdmentioning
confidence: 99%
“…Different mechanisms such as induction of hypoxia-induced factor-1 (Yuan et al, 2011), reduced inflammation (Xiong et al, 2013), inhibition of endoplasmic reticulum stress (Xu et al, 2021) and inhibition of autophagy (Zhang et al, 2022) (Guerreiro et al, 2015;Liu et al, 2018b), though there are still confounding factors in these. One such study reports a functional motor improvement by exogenous orexins in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) -induced PD mouse model (Wang et al, 2019b).…”
Section: F Orexins In Inflammation and Neuronal Cell Plasticity And D...mentioning
confidence: 99%
“…At least in part, this effect may result from enhanced sleep-related brain glymphatic clearance of metabolic by-products, such as amyloid-β [ 159 , 160 ]. On the other hand, studies on mouse models show that orexins can ameliorate parkinsonian motor deficits by increasing the spontaneous activation of pallidal neurons [ 161 ].…”
Section: Orexin Cancer and Neurodegenerative Diseasesmentioning
confidence: 99%